Government-subsidized R&D and firm innovation: evidence from China - Guo, Di; Guo, Yan; Jiang, Kun (Elsevier, 2016)
This study investigates the effects of government R&D programs on firm innovation outputs, which are measured by the number of patents, sales from new products, and exports. Particularly, we examine the effects of Innovation Fund for Small and Medium Technology-based Firms (Innofund), which is one of the largest government R&D programs that support R&D activities of small and medium-sized enterprises in China. Using a panel dataset on Chinese manufacturing firms from 1998 to 2007, we find that Innofund-backed firms generate significantly higher technological and commercialized innovation outputs compared with their non-Innofund-backed counterparts and the same firms before winning the grant. Moreover, the changes in the governance of Innofund in 2005 from a centralized to a decentralized one because of policy amendments have significant effects on the effectiveness of the program. Specifically, the magnified effects of Innofund on technological innovation outputs become significantly stronger after the governance of Innofund becomes more decentralized. Identification problems are addressed by utilizing both propensity score matching and two-stage estimation approaches.